The Impact of Toxic Relationships on Depression and Anxiety in Early Adulthood: A Systematic Review - Oktaviona, Nabilla; Iswinarti (Indonesian Journal Publisher, 2025)
This study aims to analyze the impact of toxic relationships on mental health, self-esteem, academic performance, and interpersonal conflict through a systematic literature review (SLR) approach. Utilizing 14 empirical articles from databases such as Elsevier, Springer, and Scopus, the study identifies that toxic relationships trigger mental health disorders (35%), decreased self-esteem (24%), reduced academic performance (18%), and interpersonal conflict (24%). Factors such as emotional abuse, cultural norms, and social media exacerbate these impacts, particularly among adolescents and university students. Findings highlight the need for evidence-based interventions, such as solution-focused brief counseling, mindfulness, and communication education, to mitigate negative effects. This study provides an empirical foundation for developing culturally sensitive, community-based mental health programs to support psychological and social well-being.